2023
DOI: 10.3233/thc-220138
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a digital health module for undergraduate medical students: A comparative study on knowledge and attitudes

Abstract: BACKGROUND: Digital competencies are more and more required in everyday work, and training future healthcare professionals in digital health is highly important. OBJECTIVE: Aim of this study was to assess medical students’ gain of knowledge by participation in a teaching module “Digital Health”, and to evaluate their attitudes towards digital health and its role in medical education. METHODS: Students of the module were asked to complete a questionnaire and a multiple-choice-test before and after completing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, the need to develop and improve digital health competencies for medical learners and broadly for health-related students and professionals is an established objective worldwide [45,50,51]. As a fact, prior studies evaluating digital health competencies among German medical students have shown a significant improvement after a digital health teaching course was introduced in their curriculum, although most students found that digital health is not sufficiently taught in undergraduate medical education, while it may influence everyday work of physicians [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, the need to develop and improve digital health competencies for medical learners and broadly for health-related students and professionals is an established objective worldwide [45,50,51]. As a fact, prior studies evaluating digital health competencies among German medical students have shown a significant improvement after a digital health teaching course was introduced in their curriculum, although most students found that digital health is not sufficiently taught in undergraduate medical education, while it may influence everyday work of physicians [52].…”
Section: Discussionmentioning
confidence: 99%
“…One example would be the focused teaching in "Digital Health" at Charité university hospital in Berlin [14]. By implementing a digital health module for undergraduate medical students at Charité, "increased awareness for the importance and potential future impact of digital health on physicians' work" could be shown [15].…”
Section: Local Findingsmentioning
confidence: 99%
“…Curricula should prioritize digital literacy to transcend to practice in health systems (PONCETTE et al, 2020;SEEMANN et al, 2023). Health education tends to lag behind technological advances and leaves many professionals unprepared to provide care with digital skills (WALSH; RUMSFELD, 2017).…”
Section: Connecting Expertise Multidisciplinary Development For the F...mentioning
confidence: 99%